Immunohistochemical localization of spatacsin in α‐synucleinopathies. Issue 2 (22nd September 2013) - Kuru, Satoshi; Yoshida, Mari; Tatsumi, Shinsui; Mimuro, Maya
<x xml:space="preserve">Abstract</x> Spatacsin (SPG11) is a major mutated gene in autosomal recessive spastic paraplegia with thin corpus callosum (ARHSP‐TCC) and is responsible for juvenile Parkinsonism. To elucidate the role of spatacsin in the pathogenesis of α‐synucleinopathies, an immunohistochemical investigation was performed on the brain of patients with Parkinson's disease (PD), dementia with Lewy bodies (DLB) and multiple system atrophy (MSA) using anti‐spatacsin antibody. In PD, Lewy bodies (LBs) in the brain stem were positive for spatacsin. These LBs showed intense staining in their peripheral portions and occasionally in the central cores. Lewy neurites were also spatacsin‐positive. In DLB, cortical LBs were immunolabeled by spatacsin. In MSA, glial cytoplasmic inclusions (GCI) and a small fraction of neuronal cytoplasmic inclusions (NCI) were positive for spatacsin. The widespread accumulation of spatacsin observed in pathologic α‐synuclein‐containing inclusions suggests that spatacsin may be involved in the pathogenesis of α‐synucleinopathies.